Biological Treatment of Agro-Processing Effluents Using Mycofiltration for Improved Maize Root Development in Cross River State, Nigeria - Victoria Francis Ediene; Peggy O. Willie; Ekama Derrick Elemi; Mary-Ibenreh O. Agba; Ene Emmanuel Aki; Benjamin O. Unuigbe (Agro Bali : Agricultural Journal, 2026)
Untreated agro-processing effluents pose a significant and growing threat to soil and water quality in developing economies, underscoring the need for low-cost, environmentally sound biological treatment options. This study evaluated mycofiltration as a biological treatment for effluents from cassava, maize, palm oil mills, and abattoirs. Four fungal species: Shiitake (Lentinula edodes), Brick top (Hypholoma sublateritium), Phoenix mushroom (Pleurotus pulmonarius), and King Stropharia (Stropharia annulata) were considered in this study. The experiment used a 5 × 5 factorial design, replicated three times. The study was carried out in 3 sequential phases. The first phase was a 14-day laboratory immersion trial. The second was a screen-house-pot trial. The final phase took place in a rain-fed field over one growing season. Mycofiltration reduced electrical conductivity, total dissolved solids, total suspended solids, and biological and chemical oxygen demands (BOD, COD) in cassava, maize, and abattoir effluents (p < 0.0001). Brick top and King Stropharia spawns achieved the greatest reductions. For abattoir effluent, BOD declined from 8,325.46 to 2,001.11 mg/L (76%) and COD from 13,200.12 to 6,019.81 mg/L (54%) under King Stropharia treatment. In the laboratory phase, abattoir effluent filtered with Brick top (E4M2) produced maize root lengths exceeding those of the water control by 178% (7.333 vs. 2.632 cm); this root growth benefit persisted across the screen house and field phases. Palm oil mill effluent inhibited root development by 46-53% across all phases and fungal treatments, reflecting its recalcitrant load (BOD 28,400.56 mg/L; COD 45,760.82 mg/L in raw form). The factorial ANOVA results confirmed that effluent type and mushroom spawn both significantly affect mycofiltration performance. These findings demonstrate that mycofiltration performance is effluent-specific. Findings from this study provide quantitative evidence that mushroom spawn selection must be matched to the target effluent type to achieve both compliant discharge and beneficial agricultural reuse.